(untitled) (International Journal of Business, Economics and Management, 2024)
This study was set to examine the determinants of financial performance of pension funds in Tanzania. According to literature millions of the people under the globe depend on the pension funds as their principal sources of income at their retirement age. This study adopted a descriptive design to examine the determinants of financial performance of pension funds in Tanzania. The study uses regression analysis approach to examine the effect of determinants on financial performance of pension funds. Data were collected from National Social Security Fund (NSSF)’s financial statements for the period from 2005 to 2022. Different tests were employed such as normality test, heteroscedasticity test multicolliniality test and autocorrelation test in multiple regression modelling. The findings from this study revealed that investments and contribution density have a positive relationship to return on assets. However, the age of the contributors has depicted a weak and insignificant relationship to the return on assets of the pension fund under investigation. Therefore, it is recommended that the pension funds have to put more efforts on its investments as well as contribution density which are key contributors to the financial performance of pension funds in Tanzania.